POISONOUS PLANTS DATURA STRAMONIUM - K.Giyosov; I.Raxmonqulov (Scholar Express Journal, 2022)
Datura stramonium is an annual, odorous, poisonous herb belonging to the family Solanaceae. Alkaloids, essential oils and carotene such as giostsiamine, scopolamine, atropine were found in the leaves and seeds. They are used in folk medicine and medicine against various diseases.
Keywords: Poisonous Plants; Alkaloids; Giostsiamine; Scopolamine; Atropine; Carotene